Gamma Delta T-Cell Based Cancer Immunotherapy: Past-Present-Future - Saura-Esteller, José; de Jong, Milon; King, Lisa A.; Ensing, Erik; Winograd, Benjamin; de Gruijl, Tanja D.; Parren, Paul W. H. I.; van der Vliet, Hans J. (Frontiers in Immunology, 2022)
γδ T-cells directly recognize and kill transformed cells independently of HLA-antigen presentation, which makes them a highly promising effector cell compartment for cancer immunotherapy. Novel γδ T-cell-based immunotherapies, primarily focusing on the two major γδ T-cell subtypes that infiltrate tumors (i.e. Vδ1 and Vδ2), are being developed. The Vδ1 T-cell subset is enriched in tissues and contains both effector T-cells as well as regulatory T-cells with tumor-promoting potential. Vδ2 T-cells, in contrast, are enriched in circulation and consist of a large, relatively homogeneous, pro-inflammatory effector T-cell subset. Healthy individuals typically harbor in the order of 50-500 million Vγ9Vδ2 T-cells in the peripheral blood alone (1-10% of the total CD3+ T-cell population), which can rapidly expand upon stimulation. The Vγ9Vδ2 T-cell receptor senses intracellular phosphorylated metabolites, which accumulate in cancer cells as a result of mevalonate pathway dysregulation or upon pharmaceutical intervention. Early clinical studies investigating the therapeutic potential of Vγ9Vδ2 T-cells were based on either ex vivo expansion and adoptive transfer or their systemic activation with aminobisphosphonates or synthetic phosphoantigens, either alone or combined with low dose IL-2. Immune-related adverse events (irAE) were generally , but the clinical efficacy of these approaches provided overall limited benefit. In recent years, critical advances have renewed the excitement for the potential of Vγ9Vδ2 T-cells in cancer immunotherapy. Here, we review γδ T-cell-based therapeutic strategies and discuss the prospects of those currently evaluated in clinical studies in cancer patients as well as future therapies that might arise from current promising pre-clinical results.